(untitled) (Journal of actual problems of jurisprudence, 2019)
The author of this article carries out the analysis of the new draft of the Criminal code where opens the following problem questions: a) adoptions of the criminal legislation have to be carried out according to the Constitution, and also standards of the international treaties ratified by Kazakhstan; b) realization of the main directions of development of criminal law has to be carried out within the Concept of legal policy; c) standards of the code have to raise level of security of the rights and freedoms of citizens. It is emphasized in the work that the main emphasis of a criminal legal mechanism of regulation of the public relations has to be laid on prevention of criminal behavior. Keywords: Criminal code, criminal, criminal law, criminology, security, prevention, criminal legal mechanism.